2014
DOI: 10.2196/mhealth.3882
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Health Intervention for Self-Management and Lifestyle Change for Persons With Type 2 Diabetes, Part 2: One-Year Results From the Norwegian Randomized Controlled Trial RENEWING HEALTH

Abstract: BackgroundSelf-management is crucial in the daily management of type 2 diabetes. It has been suggested that mHealth may be an important method for enhancing self-management when delivered in combination with health counseling.ObjectiveThe objective of this study was to test whether the use of a mobile phone–based self-management system used for 1 year, with or without telephone health counseling by a diabetes specialist nurse for the first 4 months, could improve glycated hemoglobin A1c (HbA1c) level, self-man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
339
2
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 252 publications
(371 citation statements)
references
References 45 publications
8
339
2
22
Order By: Relevance
“…Among the 6 studies included in the meta-analysis, one[17] that performed a three-arm study that included two intervention groups and one control group, and another performed a four-arm study[19] that included three intervention groups and one control group. All six studies of the meta-analysis included personalized feedback from a healthcare practitioner to the patient or other healthcare provider regarding the clinical data uploaded.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 6 studies included in the meta-analysis, one[17] that performed a three-arm study that included two intervention groups and one control group, and another performed a four-arm study[19] that included three intervention groups and one control group. All six studies of the meta-analysis included personalized feedback from a healthcare practitioner to the patient or other healthcare provider regarding the clinical data uploaded.…”
Section: Resultsmentioning
confidence: 99%
“…The final instrument has eight scales, which have been translated and culturally adapted into over 20 languages, and are currently being applied in clinical trials worldwide, including in Norway [12][13][14][15]. However, only a few studies have reported the psychometric performance of the heiQ in the diverse settings, in which it is being applied [16][17][18][19][20][21][22].…”
Section: Making Robust Decisions About the Impact Of Health Educationmentioning
confidence: 99%
“…It has been shown previously how integrated daily use is more likely if the self-management components are offered in a mobile phone app, and electronic diaries are thought to improve self-management. 6,7 Certainly the patient should be the primary "user" of that data, but even the most The use of smartphone technology allows for a freer interchange between patients and the health care team.…”
Section: Discussionmentioning
confidence: 99%